Activation of citizen responders to out-of-hospital cardiac arrest. Issue 3 (June 2021) - Folke, Fredrik; Andelius, Linn; Gregers, Mads Tofte; Hansen, Carolina Malta
Abstract : Purpose of review: To discuss different approaches to citizen responder activation and possible future solutions for improved citizen engagement in out-of-hospital cardiac arrest (OHCA) resuscitation. Recent findings: Activating volunteer citizens to OHCA has the potential to improve OHCA survival by increasing bystander cardiopulmonary resuscitation (CPR) and early defibrillation. Accordingly, citizen responder systems have become widespread in numerous countries despite very limited evidence of their effect on survival or cost-effectiveness. To date, only one randomized trial has investigated the effect of citizen responder activation for which the outcome was bystander CPR. Recent publications are of observational nature with high risk of bias. A scoping review published in 2020 provided an overview of available citizen responder systems and their differences in who, when, and how to activate volunteer citizens. These differences are further discussed in this review. Summary: Implementation of citizen responder programs holds the potential to improve bystander intervention in OHCA, with advancing technology offering new improvement possibilities. Information on how to best activate citizen responders as well as the effect on survival following OHCA is warranted to evaluate the cost-effectiveness of citizen responder programs.